Contractor’s design responsibility in Malaysian traditional and design and build construction contracts: a legal perspective / Abd Hamid Abd Rahman … [et al.] - Abd Rahman, Abd Hamid; Ramli, Abd Rahman; Fathi, Nik Hasbi; Mohamed, Noriha; Muhammad, Razali (2010)
Much as we desire not to have mishaps, we cannot avoid accidents; but we can certainly minimize its occurrence. This is a research in one of the contributing factors to structural failure: the design. It analyses the extent of contractor design responsibility by providing the legal insight into the extent of liability for contractors between two types of procurement contracts in Malaysia: the design and build and traditional methods. The focus of the research is on design liability in torts as this is where the development of the case laws is more pronounced. Selected cases from the UK, Canada, Australia and Singapore show that the courts readily emphasize liability greater on design and build contractor, adopting the higher standard, compared to the exercise of reasonable skill and care for the traditional contractor. Within the setting of the design and build contract, the contractor owes the highest liability, where fit-for-purpose liability is implied even in absence of the contractual provisions. Their liability can extend even to the end user when latent defects manifest themselves by the designer builder. The standard of care expected of the consultant is limited to the exercise of reasonable skill and care, although exceptions arise when fit-for-purpose liability can be transferred by the contractor. The research concludes with the findings that the case law in Malaysia has not developed as extensive as other jurisdictions in the commonwealth, placing uncertainty of direction if ever a case on design failure undertaken by a contractor comes to court. As such, the recommendations are for clear express contractual provisions be made in the standard forms and awareness be raised among the contractors, sub-contractors and the consultants for the design duties and responsibilities to minimize occurrence of structural design failures.